Coresistance to Zidovudine and Foscarnet Is Associated with Multiple Mutations in the Human Immunodeficiency Virus Type 1 Reverse Transcriptase - Tachedjian, Gilda (American Society for Microbiology, 1998)
Human immunodeficiency virus type 1 (HIV-1) isolates obtained from a patient with AIDS were assessed for coresistance to foscarnet and zidovudine. An HIV-1 strain (AP20) coresistant to foscarnet and zidovudine was isolated after 20 months of continuous combination therapy. The reverse transcriptase (RT) gene of AP20 had 41 substitutions which were different from the HXB2-D sequence and 9 that were different from the sequence of its foscarnet-sensitive, zidovudine-resistant progenitor virus (AP6). Six of these mutations were nonpolymorphic (T39A, V108I, K166R, K219R, K223Q, and L228R). Both strains had the conventional mutations mediating zidovudine resistance. In vivo selection may result in HIV-1 strains that are coresistant to foscarnet and zidovudine, but coresistance appears to require a complex evolutionary path and multiple RT mutations.